2021
DOI: 10.1002/eji.202049033
|View full text |Cite
|
Sign up to set email alerts
|

Innate lymphoid cells and cancer: Role in tumor progression and inhibition

Abstract: Innate lymphoid cells (ILCs), a critical component of the immune system, have recently been nominated as emerging players associated with tumor progression and inhibition. ILCs are classified into five groups: natural killer (NK) cells, ILC1s, ILC2s, ILC3s, and lymphoid tissue inducer (LTis) cells. NK cells and ILC1s are mainly involved in antitumor activities due to their cytotoxic and cytokine production capabilities, respectively. The current understanding of the heterogeneous behavior of ILC2s and ILC3s in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 129 publications
(299 reference statements)
0
22
0
Order By: Relevance
“…Although, type 2 responses by ILC2s have classically been associated with the promotion of TME; in a study carried out in a mouse model of lymphoma, it was reported that if ILCs were activated by stimuli such as IL-33, they could develop an immune protection resulting in decreased tumour growth [ 359 ] and in an indirect support of anti-tumour immunity by enhancing both, MHC-I expression on DCs as well as T cell cytotoxicity, as described in primary and metastatic murine lung [ 172 ] ( Table 1 ). In support of this, in mouse lung cancer [ 171 ], also IL-33 was related to good prognosis since it could elevate the frequency of tumour infiltrating ILC2s via CCL5, CXCL10, and CXCL12. In addition, also IL-5 has been correlated with anti-tumour activity since is capable of suppressing melanoma growth in the lung by recruiting eosinophils [ 360 ].…”
Section: Dual Effect Of Immune Cells In Cancermentioning
confidence: 80%
See 2 more Smart Citations
“…Although, type 2 responses by ILC2s have classically been associated with the promotion of TME; in a study carried out in a mouse model of lymphoma, it was reported that if ILCs were activated by stimuli such as IL-33, they could develop an immune protection resulting in decreased tumour growth [ 359 ] and in an indirect support of anti-tumour immunity by enhancing both, MHC-I expression on DCs as well as T cell cytotoxicity, as described in primary and metastatic murine lung [ 172 ] ( Table 1 ). In support of this, in mouse lung cancer [ 171 ], also IL-33 was related to good prognosis since it could elevate the frequency of tumour infiltrating ILC2s via CCL5, CXCL10, and CXCL12. In addition, also IL-5 has been correlated with anti-tumour activity since is capable of suppressing melanoma growth in the lung by recruiting eosinophils [ 360 ].…”
Section: Dual Effect Of Immune Cells In Cancermentioning
confidence: 80%
“…In human decidua, molecules present in the TME, such as TGF-β can induce NK cell conversion to ILC1s with pro-angiogenic and immune tolerant features [ 174 ], as described in mouse melanoma. In human and mouse NSCLC (eomesdormin downregulation in NKp46 + NK1.1 + of ILC1s) and CRC patients (because of inhibitory receptors expression, such as Klre1 and Klra7) ILC1s have also associated with pro-tumoural functions [ 171 ] ( Table 1 ).…”
Section: Dual Effect Of Immune Cells In Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…Specific alterations in the cytokine concentrations in the tumor microenvironment result in different changes in ILC composition. In the tumor microenvironment, ILC composition and functions are heavily influenced by the different cytokines, immune cells and immunosuppressive milieu which can lead to their trans differentiation into other subsets leading to a pro or anti-tumor role ( 34 , 38 , 50 55 ). Here, we summarize the findings from numerous murine and human studies describing the plasticity of ILC subsets in homeostasis and pathological conditions with a focus on ILCs in the tumor microenvironment.…”
Section: Ilc Plasticitymentioning
confidence: 99%
“…In the context of cancer, ILCs can have either pro- or anti-tumoral effects ( 4 ). The mechanistic determinants of these effects are yet to be understood, but are largely dependent on the interplay between the particular ILC subset and the microenvironment of the diseased tissue ( 5 ). The described plasticity of ILCs poses added complexity.…”
Section: Introductionmentioning
confidence: 99%